The Effect of Health Education on the Implementation of Foot Gymnastics Using Audiovisual Methods on Increasing Knowledge of Diabetics - Syaipuddin; Yasir Haskas; Sitti Nurbaya; Hasnita; Rahmawati; Suhartatik (International Journal of Public Health Excellence (IJPHE), 2023)
Diabetes mellitus has increased due to several factors, one of which is knowledge. Thus, increasing knowledge can be applied in many ways, one of which is to provide teaching using audiovisual methods. The type of research used is quassy experiment design research design with one group pre test-post test design. In this study, initial knowledge of the sample will be tested before the intervention (pretest) and after the intervention (posttest). Providing foot gymnastics education through audiovisual media and demonstration methods can increase the knowledge and ability of people with type 2 diabetes in doing foot exercises. A positive rating with an N value of 48, which means that out of 54 respondents, the pre and post test scores increased with a mean rank or average increase of 21.00 and the number of ratings was 861.00. The obstacle value is N 7, meaning that there are 7 respondents with the same score between the previous test and the final test. Based on the results of statistical tests, a significance value of 0.000 is obtained which means that H0 is rejected because of the significance value of p <; 0.05 and Ha is accepted, it can be concluded that foot motor education through audiovisual affects the knowledge of diabetics.The use of audiovisual media and demonstration methods can be used by puskesmas nurses as a means of advertising and prevention of diabetic ulcer complications to improve the quality of life of patients with type 2 diabetes.